PENGEMBANGAN KOMPETENSI PROFESIONAL GURU PRODUKTIF SMK - nurjanah, iis (Wali Pikir: Journal Of Education, 2023)
This research is based on the importance of improving the professionalism of teachers, especially private vocational teachers in KORWIL III District Bandung in developing competence through the existing activities in Korwil. This research uses qualitative method with "phenomological naturalistic" approach adopted from Bogdan and and Biklen (I982). This approach puts researchers as the main instrument to directly visit the data source. Document were collected through observation, interview and documentation. Document are expressed in terms of words and analyzed by inductive analysis by expressing the meaning of the observed state. The results of this study reveal: (1) Planning of Professional Teacher Competency Development Activity of SMK begins with a policy undertaken with a) Conducting Activities (KKG) b) obliging (KKG) in each region c) Implementation (KKG) supervised, monitored and evaluated (2) Implementation through KKG work program, namely : general program, core / core, and supporting (3) Evaluation of teacher performance is done by each principal who later reported to the supervisor, by: 1) Observing class activities 2) Review of notes 3) involving various parties as evaluators, (4) Supporting factors a) idealism and work motivation of teachers, educational qualifications, coordination and cooperation among teachers, with Principals and coaches and roles as well as the community. The inhibiting factors are the condition of schools that have not been fully conducive, the lack of balanced rewards, the low welfare received by teachers, and the limited infrastructure. (5) Teachers' participation in productive SMK KKG activity in KORWIL III Bandung regency present well enough with adequate participation and creativity. (6) The advantage of obtaining new information, increasing insight, knowledge and skills, getting a charter.